Optimalisasi Manajemen Sumber Daya Data Untuk Mengatasi Tantangan Digitalisasi Dalam Operasional Bank Syariah - Deviana Sari; Rissa Jahara; Tengku Raihan Dalila; Nurbaiti Nurbaiti (Jurnal Riset Ekonomi dan Akuntansi, 2024)
This research focuses on the characteristics of digital banking that are relevant in overcoming the challenges of digital money services from non-bank applications in Islamic banking operations in Indonesia, especially in the context of data resource management. Key characteristics highlighted include predictability, interoperability, speed, security and mobility. The research results show that data resource management is core in optimizing sharia bank operations to compete with non-bank applications that increasingly dominate. Islamic banks must ensure data certainty and security, and utilize data efficiently to meet increasingly polarized customer needs. In facing competition from non-bank applications, Islamic banks must continue to innovate, understand consumers, and optimize data resource management to remain relevant in the digital banking era.